Comprehensive analysis on the energy resilience performance of urban residential sector in hot-humid area of China under climate change. (January 2023) - Zou, Yukai; Deng, Yuwen; Xia, Dawei; Lou, Siwei; Yang, Xiaolin; Huang, Yu; Guo, Jialiang; Zhong, Zhengnan
Highlights: Energy resilience of residential sectors under climate change are evaluated. Uncertainties in climates, building characteristics and use patterns are considered. The energy demand of residential sector in hot-humid area can rise by 102.2%. Building with a high shape coefficient value tends to be more affected by climate. Family pattern is another important factor that influences the energy trend. Abstract: Residential sector is one of the main consumers of the energy market. This study conducts a comprehensive analysis on the future energy resilience performance of urban residential sector in hot-humid area of China in the 21 st century. Uncertainties, including future climate, building characteristic and occupancy behavior, are considered in future energy projections. Since the local climate is characterized by hot summer and warm winter, and local building energy is cooling-dominated, this study focuses on the changes in future cooling load. The results indicate that future energy demand of residential sector in hot-humid areas will increase over time except under the Shared Socioeconomic Pathway (SSP) 1-2.6, and the magnitude of the rise could be significant. Under the SSP5-8.5, the most severe scenario for climate change, the average annual energy demand of residential sector in the long-term future is about 90 kWh/m 2, which is above twice the energy demand under current typical climate. The annual building energy fluctuates more in a hotter future. Energy demands of dwellings with different building forms and use patterns may vary disproportionately in the changing climate. The framework and findings could give implications on future energy system design in cities. Graphic abstract: Image, graphical abstract